Empowering Women in Fisheries: A Gender-Transformative Journey in Muleba District of Kagera Region in Tanzania - Kakwasha, Keagan; Mudege, Netsayi; Kilanga, Lucyphine; Chileya, Agness (WorldFish, 2024)
This outcome story is based on work implemented in Muleba District by WorldFish, the Tanzania Women Fish Workers Association (TAWFA), which is the Tanzanian chapter of the African Women Fish Processors and Traders Network (AWFISHNet), and the Environmental Management and Economic Development Organization (EMEDO). In Muleba, traditional gender norms have long restricted women’s access to resources, as well as their decision-making power and mobility, particularly within fish value chains. These challenges are further exacerbated by the growing impacts of climate change, which disproportionately affect women’s livelihoods in fisheries. HER+ addresses these barriers through a gender-transformative approach. This outcome story highlights how the Initiative builds on work previously done by EMEDO, has increased women’s participation in the fisheries value chain, and has fostered a significant shift in societal attitudes, resulting in enhanced resilience to climate change.